2019
DOI: 10.1038/s41598-019-39943-3
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion mechanism and kinetics of Al-Zn coating deposited by arc thermal spraying process in saline solution at prolong exposure periods

Abstract: Steel structures significantly degrades owing to corrosion especially in coastal and industrial areas where significant amounts of aggressive ions are present. Therefore, anodic metals such as Al and Zn are used to protect steel. In the present study, we provide insights for the corrosion mechanism and kinetics of Al-Zn pseudo alloy coating deposited on mild steel plate via an arc thermal spraying process in 3.5 wt.% NaCl solution in terms of its improved corrosion resistance properties at prolonged exposure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 77 publications
0
12
0
2
Order By: Relevance
“…The presence of phases was determined by XRD and results are shown in Figure 4c. The XRD results show that the Zn-Al coating mainly contain Zn and Al (Figure 4c) phases which is a parent metal used for the deposition of the coating [28]. There is no other phase found rather than Zn and Al as revealed by XRD.…”
Section: Sem and Xrd Of Zn-al Coatingmentioning
confidence: 91%
See 3 more Smart Citations
“…The presence of phases was determined by XRD and results are shown in Figure 4c. The XRD results show that the Zn-Al coating mainly contain Zn and Al (Figure 4c) phases which is a parent metal used for the deposition of the coating [28]. There is no other phase found rather than Zn and Al as revealed by XRD.…”
Section: Sem and Xrd Of Zn-al Coatingmentioning
confidence: 91%
“…The arc thermal metal spraying method (ATMSM) was used to address the problem of metal plate in construction for existing shielding facilities owing to the cost effectiveness. In the arc thermal metal spraying method, a metal wire rod is coming out from the nozzle of a spray gun that blows compressed air, and is dispersed and cooled on the surface of the specimen to be coated [14,[28][29][30][31][32][33][34][35][36][37]. Subsequently, the specimen after spraying is allowed to quench, solidify, and laminate.…”
Section: Experiments Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher coating thickness reduces the penetration of chloride ions, thus the corrosion resistance properties of the Al coating can be improved [22]. Some of the researchers have used alloying of Zn, Si, Mg, and rare earth metals with Al using thermal spray process onto the steel substrate and found that the corrosion resistance properties of the coating have increased owing to the deposition of corrosion products in the pores/defects of the coating [23][24][25][26][27][28]. There are many sealants such as organic, inorganic, polymer, ceramic, etc.…”
mentioning
confidence: 99%